Aid for Trade: an opportunity for re-thinking German aid for growth - Michael Brüntrup; Petra Voionmaa (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Aid for Trade (AfT) is a new concept for a variety of activities carried out to support the ability of developing countries to engage in trade. What is new in AfT is its bundling of these activities under one roof, its institutional and political links, particularly its embeddedness in trade agendas, and its strong orientation towards trade and competitiveness. The European Union (EU), i.e. the European Commission and the member states, has made commitments to increase AfT in quantity and quality, and to advance its AfT agenda on a joint basis. Some efforts to put these commitments into practice are under way. However, challenges remain for both the quantity and quality of AfT implementation. As a member of the EU, Germany is committed to further integrating the AfT agenda into its aid strategy. German aid has a wealth of priority areas, instruments, agencies and experience, and a reputation for implementing AfT. It is argued that AfT presents an excellent opportunity to achieve more coherence among these elements. Care must be taken to coordinate at the consistent strategies, policies and programmes in which trade plays its due (but not excessive) role, and to align AfT with these plans.
Keywords: 330